Cytogenetic and histological studies of the brook trout, Salvelinus fontinalis (Mitchill), and the Arctic char, S-alpinus (L.) hybrids - Ocalewicz, Konrad (2014)
Although brook trout and the Arctic char hybrids are able to reproduce, individuals with decreased fertility or even fish that are unable to produce any gametes have been also described. Abnormal gonadal development and disturbances in the gamete production in the char hybrid offspring may be triggered by the odd chromosome number and disturbances in their pairing during meiosis. To verify this hypothesis, cytogenetic examination and the gonadal histology analysis of the brook trout x Arctic char hybrids were carried out. Diploid chromosome number in the studied char (F-1) hybrids varied from 82 to 84 (FN = 99-102). Among 28 hybrids, 12 males, three females, nine intersex individuals and two sterile specimens were described. In the case of two individuals, gonads were not found. Diploid chromosome numbers in the males and intersex individuals varied from 82 to 84. Chromosome numbers in the females were 82 and 83 chromosomes. Two sterile fish exhibited karyotypes composed of 82 and 84 chromosomes. Predominance of the ovarian component in the intersex gonads and gonadal sex ratio distortion towards the males suggested hybrid females had problems with gonadal differentiation. However, the lack of the clear relationship between chromosome number and gonadal development in the studied hybrids did not support our hypothesis that odd chromosome number may be responsible for such reproductive disturbances in the hybrid individuals. We have presumed that sterility and intersexual development of the gonads may be caused by interactions between brook trout and Arctic char genes on the sex chromosomes and autosomes rather than unpairing of the parental chromosomes.